Animals in Human Genetics Research: Models, Applications, and Ethical Considerations - Muzammal, Muhammad; Khan, Aiman Saeed; Shafiq, Maria; Burki, Nazia Farid; Naz, Shaista; Malik, Hunza; Khan, Ali Ahmad; Hussain, Murtajiz; Khan, Suleman; Zada, Afsar; Fatima, Sana; Hashmi, Hamna Batool; et al. (The Nucleus, 2025)
Animal models serve as crucial research tools in human genetics research by combining scientific knowledge from laboratory findings and medicine. Biological study models while also providing the potential to create new treatments. Other species, such as rats, along with zebrafish and non-human primates, offer unique advantages when used in combination with mice in genetic studies, despite mice have been the conventional leaders due to their small size and ease of genetic modification. Rats offer better abilities in scientific studies due to their larger body size, which facilitates extensive experimental tests. These tests enable investigations of complex diseases, such as neurodegenerative disorders, cardiovascular diseases, and metabolic disorders. CRISPR-Cas9 gene editing tools have expanded the diversity of rat models, thereby enhancing their value as more accurate models for disease research. Using animals in human genetic research poses several challenges to be addressed. The three primary issues that the debate on the use of animals in scientific research is based on include the differences in biology with the various species and the ethical issues, and the expenditure of keeping the animals as models of research. The ethical factors applied in all the animal studies presented in this review have followed the established ethical principles, such as the 3Rs (Replacement, Reduction, and Refinement), to ensure humane treatment and scientific responsibility. The use of animal models, especially rats, remains significant in a holistic studies on human genetic disorders and the advancement of innovative treatment procedures. The particular aim of this review is to offer a comprehensive description of the nature, merits, and demerits of the regularly used animal models in human genetic studies to help researchers in choosing the best models to use in their studies.